Energy efficiency through user adoption of the sharing economy leading to environmentally sustainable development - Hong Lin; Xujun Zhai (Journal of Innovation & Knowledge (JIK), 2023)
The adoption of the sharing economy by organizations is of central importance to energy efficiency. However, previous studies ignore the role of user adoption of the sharing economy. Therefore, the objective of this study is to investigate the role of energy efficiency through user adoption of the sharing economy to promote environmental sustainability. This objective is achieved using a quantitative research method. Data collection is managed using a survey questionnaire. Area cluster sampling is used for the data collection because this sampling technique is suitable for dealing with a widespread population. The sample size of the study is 178. Scale items taken from previous studies are used to measure the relationships between herd behaviour, perceived usefulness, perceived ease of use, trust, behavioural intention, and environmental sustainability. The results show that energy efficiency through user adoption of the sharing economy is of key importance in the behavioural intention of users. User adoption of the sharing economy has the potential to promote environmental sustainability. The results provide valuable insights for practitioners designing strategies for energy efficiency and the sharing economy.
Keywords: P48; E02; K32; 650; Behavioural intention; Energy efficiency; Environmental sustainability; Herd behaviour; Perceived ease of use; Perceived usefulness; Sharing economy; Trust